Shingles in Pregnancy: An Elusive Case of Left Upper Quadrant Abdominal Pain - Wong, Jennifer WH (Hawaii J Med Public Health, 2018)
Pregnancy can complicate the presentation and workup of abdominal pain. A healthy 21-year-old gravida-3 para-1 woman at 34 weeks of gestation presented for severe pain localized to her abdominal left upper quadrant (LUQ. Physical exam was unremarkable except for localized pain on palpation, and she was discharged with acetaminophen and cyclobenzaprine for presumed musculoskeletal pain. The next day, she returned for worsening pain. An extensive workup including labs, electrocardiogram, chest x-ray, and abdominal computed tomography was unremarkable, and she was discharged with hydrocodone/acetaminophen. Later that evening, after two discharges, the patient presented for increased pain with new onset of vesicles in her left T6 dermatome. She was diagnosed with shingles, started on valacyclovir and gabapentin, and eventually went on to deliver a healthy infant. Shingles classically presents as excruciating pain followed by the eruption of vesicles. This case is important because it reviews the significance of shingles in pregnancy and is one of the first reports to extensively discuss the differential and workup of LUQ abdominal pain in pregnancy. Abdominal pain is a relatively common complaint during pregnancy, and a methodical approach should be taken when evaluating LUQ in pregnancy. Shingles could be considered in the differential diagnosis of pain of unclear origin.